RAMAN SPECTROSCOPY OF THE AMORPHOUS CARBON FILMS, CONTAINING SILVER NANOCLUSTERS - Prikhodko, O. Yu.; Nikitin, A. G.; Ryaguzov, A. P.; Maksimova, S. Ya.; Daineko, Ye. A.; Rusinov, A. N. (Recent Contributions to Physics, 2009)
Raman spectroscopy method have been used to study structure of the amorphous hydrogenated carbon films with silver nanoclusters a-C:H(Ag). These films were obtained by ion-plasma magnetron sputtering of the combined graphite-silver target in argon-hydrogen plasma. Raman scattering spectrums of the films with different silver concentration and various deposition temperature, were studied. It was established, that the film’s structure consist of two phases: amorphous and nanocrystalline. Increasing of silver concentration and growing deposition temperature modifies the structure of a-C:H films to the graphite like.